2013
DOI: 10.1016/j.bmc.2013.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of peptides and glycopeptides with polyproline II helical topology as potential antifreeze molecules

Abstract: A library of peptides and glycopeptides containing (4R)-hydroxy-L-proline (Hyp) residues were designed with a view to providing stable polyproline II (PPII) helical molecules with antifreeze activity. A library of dodecapeptides containing contiguous Hyp residues or an Ala-Hyp-Ala tripeptide repeat sequence were synthesized with and without α-O-linked N-acetylgalactosamine and α-O-linked galactose-β-(1→3)-N-acetylgalactosamine appended to the peptide backbone. All (glyco)peptides possessed PPII helical seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…Indeed, in a limited number of examples, including antifreeze proteins and the prion protein, dramatic structural differences were observed between modification of Ser/Thr residues with α anomers versus β anomers of sugars. 42,168,169 Data to date suggest that β anomers exhibit substantial steric effects near the backbone, similar to β-branched and aromatic amino acids, whereas α anomers are more compatible with compact protein conformations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a limited number of examples, including antifreeze proteins and the prion protein, dramatic structural differences were observed between modification of Ser/Thr residues with α anomers versus β anomers of sugars. 42,168,169 Data to date suggest that β anomers exhibit substantial steric effects near the backbone, similar to β-branched and aromatic amino acids, whereas α anomers are more compatible with compact protein conformations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, owing to their macrocyclic character, small modifications to cyclic peptides often cause massive conformational alterations. [17][18][19][20][21] Most of these methods are based on the implicit solvent model. 7,16 In the past years, several methods have been proposed to predict the three-dimensional structure of cyclic peptides using computer simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of new IRI-specific molecules/macromolecules has been pursued. Ben et al have reported that simplified glycopeptides and glycolipids have potent IRI and can enhance cryopreservation 11 12 13 . Gibson and co-workers have shown that synthetic polymers can mimic AF(G)Ps function and shown this to enhance red blood cell cryopreservation 14 15 16 .…”
mentioning
confidence: 99%